Using ignition of coal dust produced by different types of mechanical treatment under conditions of rapid heating; Combustion, Explosion, and Shock Waves; Vol. 52, iss. 3 - Chernetsky M. Yu. Mikhail Yurjevich; Burdukov A. P. Anatoly Petrovich; Butakov E. B. Evgeny Borisovich; Anufriev I. S. Igor Sergeevich; Strizhak P. A. Pavel Alexandrovich (2016, 2016)
Title screen